CRYOSPHERE OF THE EARTH AND ITS INFLUENCE ON ELECTROMAGNETIC PROCESSES IN SEISMOACTIVE MOUNTAINOUS AREAS - Bashkuev Yu.B.; Buyanova D.G.; Angarkhaeva L.Kh.; Dembelov M.G.; Khaptanov V.B.; Melchinov V.P.; Hayakawa M. (My University, 2006)
The purpose of this paper is to present a detailed physical description and classification of electrical properties, construction and structure of the cryolitozone at the depth of skin-layer in VLF range for Aldan plateau, central part of the Yakutia and tundra regions not far from the Arctic Ocean. Electrical characteristics of the regions studied are typical for the cryolitozone. The frequency dispersion of some types of permafrost zones is experimentally studied. It is then shown that the frequency dispersion of the electric resistance of the layer of frozen friable sediments over the frequency from direct current to VLF-MF ranges is a peculiarity of electrical properties of the cryolitozone. A complex interpretation of the data of radioimpedance and electric soundings for permafrost rocks is carried out on the basis of developed automated numerical methods of direct and inverse problems for the radioimpedance sounding. It is determined that geoelectrical sections with the type of K (ρ1 < ρ2 > ρ3) and the type of Q (ρ1 > ρ2 > ρ3) are most typical for sediment rocks of the cryolitozone at the depth of 100 m of the Northern-East part of Russia. Geoelectrical section A (ρ1 < ρ2 < ρ3) is the basic for ancient crystal rocks of the Aldan shield. Electrical properties of the cryolitozone are changed appropriately in space and in time and depend on the complex of the crystal and sediment rocks. The surface impedance shows inductive and capacitive nature and is changed in a wide range from minimum for saline lands to maximum for granitoids. © 2006 Elsevier Ltd. All rights reserved.
Keywords: ATTENUATION FUNCTION; CRYOLITOZONE; FREQUENCY DISPERSION; SURFACE IMPEDANCE